Current practices in cancer pain management in Asia: a survey of patients and physicians across 10 countries. (27th April 2015) - The ACHEON Working Group; Kim, Yong‐Chul; Ahn, Jin Seok; Calimag, Maria Minerva P.; Chao, Ta Chung; Ho, Kok Yuen; Tho, Lye Mun; Xia, Zhong‐Jun; Ward, Lois; Moon, Hanlim; Bhagat, Abhishek
<x xml:space="preserve">Abstract</x> Cancer patients and their physicians in 10 Asian countries were questioned on current cancer pain management practices. Improved perceptions and better regulatory policies are needed for optimal patient care. <boxed-text content-type="graphic" id="cam4471-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>